Pengaruh Terpaan Iklan Instagram terhadap Intensi Pembelian Produk Erigo Melalui Sikap terhadap Iklan dan Sikap terhadap Merek - Agnetha Faustina Germaine; Engkus Kuswarno; Kunto Adi Wibowo (Universitas Batanghari, 2023)
Advances in technology make people able to make adjustments to the rapidly advancing technology which cannot be stopped in Indonesia. Since Indonesia was shocked by the presence of a new virus known as COVID-19, many companies in Indonesia have fallen into disrepair when free trade can be carried out and this has caused industries in Indonesia, especially local businesses, to collapse, causing many to go out of business and lay off their employees. This makes business people to continue to look for solutions to be able to rise, such as making a breakthrough selling products online on social media. Businesses usually advertise their products through two features, namely Instagram Feeds and Instagram Stories. Instagram Feeds are a place where users can share and connect with others through images and videos. The purpose of this study is to determine the effect of exposure to Instragram advertising on the purchase intention of Erigo products through attitudes towards advertising and attitudes towards brands. The results in this study are consumer attitudes towards advertising and to brands. Where, both are considered forms and are very useful for marketers so that this relates to attitudes towards advertising and brands as a measuring tool to see how effectively advertisements are displayed which can later be a driver of the emergence of purchase intentions from consumers.